2018
DOI: 10.24193/adn.11.3-4.3
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Qualities and Self-Efficacy Perceptions in Character Education

Abstract: Education has an inevitable effect on character formation and through this process, teachers' role is crucial. Therefore, the aim of the study was analyzing the views of primary school teachers concerning the qualities teachers should have and their self-efficacy perceptions as character educators. This was a descriptive survey study with 301 primary school teachers from schools at different socioeconomical level. Within the study, The Qualities and Efficacies of Teacher in Character Education Scale (QETCES) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
1
10
0
2
Order By: Relevance
“…School must great pay attention to theese components. Supporting components on character education program at school have great impact on effectivity (Yolcu & Sari, 2018;Lisievici & Andronie, 2016). According to Lee, Pan, Liao, Chen, & Walters.…”
Section: Discussionmentioning
confidence: 99%
“…School must great pay attention to theese components. Supporting components on character education program at school have great impact on effectivity (Yolcu & Sari, 2018;Lisievici & Andronie, 2016). According to Lee, Pan, Liao, Chen, & Walters.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the study of Alhija (2017), wherein there is a salient difference in the students' perception of good teaching in terms of the gender of which the current study has also observed. The same idea was provided by Yolcu and Sari (2018), women teachers had higher scores regarding both importance level and self-efficacy perception of character education. The private school students also provided a significant finding in professional qualities.…”
Section: Discussionmentioning
confidence: 83%
“…Teachers' efficacy refers to the confidence of teachers in influencing and motivating students to perform well in school (Yolcu & Sari, 2018). When teachers believe in their efficacy, they will feel motivated to promote conducive learning conditions that they have created to increase the progression of academic achievement among students (Milson & Mehlig, 2002).…”
Section: Teachers' Efficacy and Implementation Of Character Educationmentioning
confidence: 99%